Cryogenic Machining of Titanium Ti-5553 Alloy - KAYNAK, YUSUF (ASME, 2019)
Titanium alloy Ti-5Al-5V-3Cr-0.5Fe (Ti-5553) is a new generation of near-beta titanium alloy that is commonly used in the aerospace industry. Machining is one of the manufacturing methods to produce parts that are made of this near-beta alloy. This study presents the machining performance of new generation near-beta alloys, namely, Ti-5553, by focusing on a high-speed cutting process under cryogenic cooling conditions and dry machining. The machining experiments were conducted under a wide range of cutting speeds, including high speeds that used liquid nitrogen (LN2) and carbon dioxide (CO2) as cryogenic coolants. The experimental data on the cutting temperature, tool wear, force components, chip breakability, dimensional accuracy, and surface integrity characteristics are presented and were analyzed to evaluate the machining process of this alloy and resulting surface characteristics. This study shows that cryogenic machining improved the machining performance of the Ti-5553 alloy by substantially reducing the tool wear, cutting temperature, and dimensional deviation of the machined parts. The cryogenic machining also produced shorter chips as compared to dry machining.
Keywords: titanium Ti-5553 alloy; cryogenic machining; machining performance; surface integrity; HIGH-PRESSURE COOLANT; TOOL-WEAR; SURFACE INTEGRITY; MACHINABILITY; DRY; DEFORMATION; MQL; MICROSTRUCTURE; PERFORMANCE; BEHAVIOR